The Influence of Phenomenon-Based Learning on Students' Critical Thinking and Communication Skills - Andi Anisa Oktobianti; Adnan; Andi Mu'nisa; Firdaus Daud; Andi Asmawati Azis (Postgraduate, University of Mataram, 2026)
This study was conducted in relation to the phenomenon-based learning approach, which aimed to determine the effect of phenomenon-based learning on students' critical thinking and communication skills. This study was a quantitative study with a multi-group pretest-posttest quasi-experimental design. In this study, there were four classes used, consisting of three classes taught using PhBL (phenomenon-based learning) with different variations, namely direct, mediated, and integrated PhBL, and one control class taught using STAD (student teams achievement division) learning. The results showed that phenomenon-based learning had a significant effect on critical thinking skills with a value of f=21.93 p<.05 and communication skills f=12.65 p<.05. Based on the three variations in PhBL learning, integrated PhBL learning showed the highest significant results in improving critical thinking skills with an average of 91.57 and communication skills of students with an average of 90.22. followed by direct PhBL learning with an average critical thinking skill of 89.48 and communication skill of 90.00, and finally mediated PhBL with an average critical thinking skill of 88.96 and communication skill of 88.45. The results of this study indicate that phenomenon-based learning is effective in improving students' critical thinking and communication skills.